A pilot study exploring the association of bronchial bacterial microbiota and recurrent wheezing in infants with atopy - Tang, Wei; Zhang, Lei; Ai, Tao; Xia, Wanmin; Xie, Cheng; Fan, Yinghong; Chen, Sisi; Chen, Zijin; Yao, Jiawei; Peng, Yi (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Compositional differences in the bronchial bacterial microbiota have been associated with asthma, but it remains unclear whether the findings can be applied to recurrent wheezing infants and to aeroallergen sensitization. Objectives: To gain insight into the pathogenesis of atopic wheezing infants and to identity diagnostic biomarkers, we used systems biology approach to analyze bronchial bacterial microbiota in recurrent wheezing infants with and without atopy. Methods: Bacterial communities in bronchoalveolar lavage from 15 atopic wheezing infants, 15 non-atopic wheezing infants, and 18 foreign body aspiration control infants were profiled by using 16S rRNA gene sequencing. Bacterial composition and community-level functions inferred from sequence profiles were analyzed for between-group differences. Results: Both the α-diversity and β-diversity were differed significantly among the groups. Compared to the non-atopic wheezing infants, the atopic wheezing infants showed a significantly higher abundance of 2 phylum (Deinococcota and unidentified_Bacteria) and 1 genus (Haemophilus) and a significantly lower abundance of 1 phylum (Actinobacteriota). Random forest predictive model for the10 genus based on OUT-based feature, suggesting that the airway microbiota had the potential to diagnose atopic wheezing infants from wheezing infants. PICRUSt2 based on KEGG hierarchical level 3, revealed that atopic wheezing-associated differences in predicted bacterial functions included Cytoskeleton protein, Glutamatergic synapse, and Porphyrin and chlorophyll metabolism pathways. Conclusion: The differential candidate biomarkers identified by microbiome analysis in our work may have reference value for the diagnosis of wheezing in infants with atopy. To confirm that, airway microbiome combined with metabolomics analysis should be further investigated in the future.